Volcaniclastic deposits: terminology and concepts for a classification in spanish - Murcia, Hugo F. (2011)
The terms used to define the clastic deposits related to volcanic activity have important implications for the society in volcanic regions. Taking into account the importance of using a common terminology when considering natural hazards in the Spanish-speaking world, this study presents a classification of volcaniclastic deposits. This classification attempts to integrate the terminology related to the formational and depositional processes (eruptive and non-eruptive) taking place at volcanoes with the resulting volcaniclastic deposits and their constituent components. The classification emphasizes on how both physical and temporal variations in volcanic activity are responsible for observed differences in the related deposits. The purpose of this classification is to be a reference for the Spanishspeaking scientific community in order to avoid the numerous inconsistencies derived from the existing translations from multiple authors. Additionally, we present a flow diagram in both Spanish and English to illustrate that this classification system can be used to define and classify consolidated/lithified, and unconsolidated deposits. The appropriate classification of volcaniclastic deposits and their constituents can ultimately improve the definition and communication of potential volcanic hazards.